Na obrzeżach socrealizmu - Hendrykowski, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2026)
The landscape of Polish art from that period, dominated by the Stalinist doctrine of Socialist Realism (socrealism), merits a scholarly reexamination today. A peculiar paradox of past research lies in the fact that (with few exceptions) it generally continues to reflect the perspective of its contemporary promoters and overseers. Did the omnipresent ideological shadow of the doctrine of socrealism truly fall over the entire territory of visual art of that time? This article uncovers a series of little-known paintings by various artists, representing an artistic alternative in Polish painting from 1949 to 1955—a period of virtually absolute socrealism dominance in culture and art.